Tyrosine nitration limits stretch-induced CD40 expression and disconnects CD40 signaling in human endothelial cells - Wagner, Andreas H.; Hildebrandt, Anke; Baumgarten, Sebastian; Jungmann, Andreas; Müller, Oliver J.; Sharov, Victor S.; Schöneich, Christian; Hecker, Markus (Blood, 2011)
Hemodynamic forces are important effectors of endothelial cell phenotype and function. Because CD40-CD154 interactions between endothelial cells and mononuclear leukocytes or activated platelets play an important role in vascular dysfunction, we investigated the effects of cyclic stretch on CD40 expression in human cultured endothelial cells. Short-term stretch transiently up-regulated CD40 expression while long-term stretch resulted in a distinct decline in CD40 protein which was prevented by inhibition of the 20S proteasome or scavenging of peroxynitrite. Tyrosine nitration of CD40 also occurred under static conditions on addition of authentic peroxynitrite, and according to mass spectrometry analysis Tyr-82 but not Tyr-31 was its target in the native protein. Immunofluorescence analysis of endothelial cells transduced with a control or Tyr-82 to Ala mutated AAV9-CD40-eGFP expression construct confirmed a peroxynitrite-dependent redistribution of the protein from the cell membrane to the cytoplasm, which was prevented by methyl-β-cyclodextrin. Moreover, CD154-stimulated IL-12p40 and E-selectin expression markedly decreased after exposure to authentic peroxynitrite or cyclic stretch, respectively. Coimmunoprecipitation demonstrated a decreased binding of TRAF2 and TRAF6 to the CD40 protein after tyrosine nitration. Through this posttranslational oxidative modification of an important costimulatory molecule, endothelial cells are able to quickly adapt to unfavorable hemodynamics and maintain their anti-inflammatory phenotype.
Gesehen am 04.11.2022